PENGARUH PENDEKATAN PEMBELAJARAN ELPSA TERHADAP KEMAMPUAN MATEMATIS SISWA - Sape, Herwandi; Muh. Ridwan (Jurnal Penalaran dan Riset Matematika, 2024)
ELPSA (Experiences, Language, Pictures, Symbols, and Application) learning approach is a method designed to improve students' mathematical understanding through direct experience, language use, visual representation, symbolization, and application in real life. This study aims to analyze the effect of ELPSA approach on the mathematical ability of grade XI students of SMK Permata Ilmu. The method used in this research is pretest-posttest design with a population of all students in grade XI of SMK Permata Ilmu and a sample of 32 students. Data were collected through mathematical ability tests before and after the application of ELPSA, which were then analyzed descriptively and inferentially using paired t-test. The results showed that there was a significant increase in the average student score from 55.31 (pretest) to 78.94 (posttest). The paired t-test resulted in a t-count value of 12.45, greater than the t-table (2.04) with a p-value (0.000) <0.05, so it can be concluded that ELPSA has a significant effect on improving students' mathematical abilities. These results support the application of ELPSA as an effective alternative learning method in improving students' mathematical concept understanding.